Pengetahuan dan Perilaku Tentang Minuman Fermentasi pada Mahasiswa - Fahira, Difa Rizki; Rasmikayati, Elly (Universitas Galuh, 2025)
Young people today often choose sugary beverages over healthier options made with fruit. A study examined the relationship between characteristics and knowledge and consumption of fermented beverages among Agribusiness students. Respondents generally had a high level of knowledge about fermented beverages, with yogurt being the most popular due to its taste. Most consumed fermented beverages once a week, with Cimory being the preferred brand. Statistical analysis revealed significant relationships between gender, residence, and pocket money with knowledge about types of fermented beverages, and between gender and residence with knowledge about their disadvantages. Additionally, significant relationships were found between gender and pocket money with types of fermented beverages consumed, frequency of illness with consumption frequency, and gender, residence, and illness with reasons for choosing specific brands.